2017
DOI: 10.1002/jbm.a.36172
|View full text |Cite
|
Sign up to set email alerts
|

The effect of four types of artificial nerve graft structures on the repair of 10‐mm rat sciatic nerve gap

Abstract: Investigating the effect of four types of artificial nerve graft (ANG) structures on rat sciatic nerve defect repair will aid future ANG designs. In this study, fibroin fibers and polylactic acid were used to prepare four ANGs with differing structures: nerve conduit with micron‐sized pores (Conduit with pore group), nerve conduit without micron‐sized pores (Conduit group), nerve scaffold comprising Conduit with pore group material plus silk fibers (Scaffold with pore group), and nerve scaffold comprising Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous studies have also shown that cellular behavior was directly influenced by the presence of microenvironment within the nerve conduits, and enhanced nerve functionality was obtained in filled conduits in comparison to the hollow nerve conduits. 48 The functional recovery can also be seen by visual observation of the toe spreading (Figure 3j−l), which was significant in case of the aCG + NGF-implanted group compared to that of the autografts group. No such toe spreading was observed for the negative control group.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have also shown that cellular behavior was directly influenced by the presence of microenvironment within the nerve conduits, and enhanced nerve functionality was obtained in filled conduits in comparison to the hollow nerve conduits. 48 The functional recovery can also be seen by visual observation of the toe spreading (Figure 3j−l), which was significant in case of the aCG + NGF-implanted group compared to that of the autografts group. No such toe spreading was observed for the negative control group.…”
Section: Resultsmentioning
confidence: 72%
“…Moreover, lumen-filled NGCs performed better than HCs as they provide a matrix for native cells attachment, proliferation, and directional growth. Previous studies have also shown that cellular behavior was directly influenced by the presence of microenvironment within the nerve conduits, and enhanced nerve functionality was obtained in filled conduits in comparison to the hollow nerve conduits . The functional recovery can also be seen by visual observation of the toe spreading (Figure j–l), which was significant in case of the aCG + NGF-implanted group compared to that of the autografts group.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in the eld of nerve repair, all researches need to be restored to the best direction and minimize negative effects. 23,24 In this study, a SA/CMCS/PPy conductive hydrogel was fabricated. SA and CMCS were crosslinked by Ca 2+ , and PPy was doped in the ECM-mimicked SA/CMCS structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the field of nerve repair, all researches need to be restored to the best direction and minimize negative effects. 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tissue engineering has developed rapidly, and many scholars have used tissue‐engineered peripheral nerves to repair and reconstruct nerve defects (Gao et al, 2015; Marconi et al, 2012; Zhou et al, 2017). In our previous studies (Zhao et al, 2013; Ma, Sun, et al, 2011; Ma, Yang, et al, 2011), our research group improved the preparation of acellular nerve scaffolds using a hypotonic buffer technique combined with freeze‐drying.…”
Section: Introductionmentioning
confidence: 99%